Does oil wealth help conserve the forests? - Wunder, Sven (2003)
A main target of environmental campaigns to save the rainforest has been to stop oil operations from damaging tropical forests. However, there is more to the oil-and-forest story than meets the eye. A comprehensive study of long-run land use changes in eight tropical oil-producing countries shows that oil wealth tends to favour higher forest-cover conservation, as oil's powerful macroeconomic effects curtail both logging and agricultural expansion. This findings implies that other financial transfers to developing countries, such as debt relief or remittances, are likely to have similar protective effects on the environment.